Postpartum Treatment of a Herniation of the Anterior Uterine Wall due to Remains of Placenta Increta - Anis Haddad; Olfa Zoukar; Houda Mhabrich; Awatef Hajjeji; Raja Faleh (Case Reports in Obstetrics and Gynecology)
In recent years, the incidence of placenta accreta and associated complications has increased significantly. The authors report the case of a pregnant woman in the 5th month of pregnancy for premature rupture of the membranes. The placenta was inserted low. The evolution was marked spontaneous work followed by the expulsion of the fetus. The delivery of the placenta was haemorrhagic and incomplete. Ultrasonic testing showed a placental fragment integrated in the thickness of the myometrium. Conservative treatment with methotrexate was published a few days later and MRI showed that the anterior uterine sac was filled with blood clots associated with pelvic effusion. A laparotomy was then performed to resect the pouch and the one-piece fragment. The follow-up was uneventful.